2013
DOI: 10.1021/ol4005992
|View full text |Cite
|
Sign up to set email alerts
|

N-Indolyltriethylborate: A Useful Reagent for Synthesis of C3-Quaternary Indolenines

Abstract: N-Indolyltriethylborate was found to be a useful reagent for dearomatizing C3-alkylation of 3-substituted indoles with both activated and nonactivated alkyl halides to give C3-quaternary indolenines, pyrroloindolines, furoindoline, and hexahydropyridoindoline under mild reaction conditions. The utility of these reagents was demonstrated in the syntheses of a pyrroloindoline-4-cholestene hybrid and debromoflustramine B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 55 publications
(16 reference statements)
0
38
0
Order By: Relevance
“…Gratifyingly, complete regioselectivity was achieved, with the C3-alkylated adducts being exclusively produced. Notably, while few metal-mediated protocols exist for the C3benzylation of 2,3-disubstituted 1H-indoles, [22] this chemistry offers the first methodology for the direct construction of indolenines adorned with a phenacyl moiety at C3 (4 b,c and 4 e). Of particular interest are the substrates with a pendant nucleophile, which cyclize onto the imine of 4 under the reaction conditions (Figure 3 e).…”
mentioning
confidence: 99%
“…Gratifyingly, complete regioselectivity was achieved, with the C3-alkylated adducts being exclusively produced. Notably, while few metal-mediated protocols exist for the C3benzylation of 2,3-disubstituted 1H-indoles, [22] this chemistry offers the first methodology for the direct construction of indolenines adorned with a phenacyl moiety at C3 (4 b,c and 4 e). Of particular interest are the substrates with a pendant nucleophile, which cyclize onto the imine of 4 under the reaction conditions (Figure 3 e).…”
mentioning
confidence: 99%
“…For this purpose, after the sequential exposure of 4 to potassium tert ‐butoxide and triethylborane (allowing the formation of an indolyltriethylborate species), farnesyl bromide ( 8 ) served as the electrophile (Scheme ) . Under these conditions, complexation of the indole anion is supposed to enhance the C‐3 nucleophilicity by electron enrichment, therefore allowing the C‐3 quaternization.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, after the sequential exposure of 4 to potassium tert-butoxide and triethylborane (allowing the formation of an indolyltriethylborate species), farnesyl bromide (8) [10] served as the electrophile (Scheme 2). [11][12][13] Under these conditions, complexation of the indole anion is supposed to enhance the C-3 nucleophilicity by electron enrichment, therefore allowing the C-3 quaternization. The direct trapping of the transitory indolenine by the appended diketopiperazine moiety allowed the formation of the tetracyclic ring system of drimentines just as in the biosynthetic proposal.…”
Section: Resultsmentioning
confidence: 99%
“…[9c-g] Intramolecular reactions can overcome the regioselectivity issues associated with intermolecular indole reactivity. [11] Several asymmetric indole C2-allylation procedures have been developed following this approach. [12] However,t hese strategies almost always lead to the formation of annulated C2-allylated indoles.Asearch of the literature revealed that the sole exception to this generalization comes from Tambar et al [13] who developed an innovative intramolecular route to branched, highly enantioenriched C2-allylated 3-amino indoles employing an enantioselective aza-Claisen rearrangement (Scheme 1, c).…”
Section: Introductionmentioning
confidence: 99%